Sex differences in general knowledge domains - Lynn, Richard (Array, 2009)
The aim of this study was to investigate some cognitive differences in highly comparable (according to age, education and motivation) samples of female and male university graduates in Croatia. Female (N=280 ; age X=26.59 ; SD=2.84)and male participants (N=96 ; age X=26.99 ; SD=2.99) were university graduates in economics, law humanities and social sciences applying for positions in public service. As part of the selection procedure, they were given a number of cognitive tests. The results were that men obtained higher average scores on the g-factor intelligence test, on the general knowledge tests of natural and social sciences, world religion and customs, and knowledge of current affairs. There were no significant sex differences on vocabulary, foreign language ability and general knowledge of culture. An analysis of covariance, with intelligence test as a covariate, showed that sex differences in general knowledge were present when intelligence was controlled.